Auditory and motion metaphors have different scalp distributions: an ERP study - Schmidt-Snoek, Gwenda L.; Drew, Ashley R.; Barile, Elizabeth C.; Agauas, Stephen J. (Frontiers in Human Neuroscience, 2015)
While many links have been established between sensory-motor words used literally (kick the ball) and sensory-motor regions of the brain, it is less clear whether metaphorically used words (kick the habit) also show such signs of “embodiment.” Additionally, not much is known about the timing or nature of the connection between language and sensory-motor neural processing. We used stimuli divided into three figurativeness conditions – literal, metaphor, and anomalous – and two modality conditions – auditory (Her limousine was a privileged snort) and motion (The editorial was a brass-knuckle punch). The conditions were matched on a large number of potentially confounding factors including cloze probability. The electroencephalographic response to the final word of each sentence was measured at 64 electrode sites on the scalp of 22 participants and event-related potentials calculated. Analysis revealed greater amplitudes for metaphorical than literal sentences in both 350-500ms and 500-650ms timeframes. Results supported the possibility of different neural substrates for motion and auditory sentences. Greater differences for motion sentences were seen in the left posterior and left central electrode sites than elsewhere on the scalp. These findings are consistent with a sensory-motor neural categorization of language and with the integration of modal and amodal information during the N400 and P600 timeframes.